2008
DOI: 10.1103/physreva.77.012719
|View full text |Cite
|
Sign up to set email alerts
|

Two-color photoassociation spectroscopy of ytterbium atoms and the precise determinations ofs-wave scattering lengths

Abstract: By performing high-resolution two-color photoassociation spectroscopy, we have successfully determined the binding energies of several of the last bound states of the homonuclear dimers of six different isotopes of ytterbium. These spectroscopic data are in excellent agreement with theoretical calculations based on a simple model potential, which very precisely predicts the s-wave scattering lengths of all 28 pairs of the seven stable isotopes. The s-wave scattering lengths for collision of two atoms of the sa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
269
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(287 citation statements)
references
References 37 publications
15
269
2
1
Order By: Relevance
“…using the homonuclear C 6 coefficients for A-A [40] and Yb-Yb [41] and the static polarizabilities α(0) for the alkali-metal atoms [40] and Yb [42]. Equation (11) gives C 6 coefficients well within 1% of the values of Ref.…”
Section: Potential Energy Curvesmentioning
confidence: 97%
“…using the homonuclear C 6 coefficients for A-A [40] and Yb-Yb [41] and the static polarizabilities α(0) for the alkali-metal atoms [40] and Yb [42]. Equation (11) gives C 6 coefficients well within 1% of the values of Ref.…”
Section: Potential Energy Curvesmentioning
confidence: 97%
“…Photoassociation spectroscopy has been carried out for bosons [12,13] as well as fermions [14]. A two-color photoassociation experiment has allowed a precise determination of the ground state s-wave scattering lengths for all combinations of Yb isotopes [15]. Finally, it was demonstrated that the significant change of the scattering properties for colliding ground state atoms can be achieved with optical Feshbach resonances in these systems [16].…”
Section: Introductionmentioning
confidence: 99%
“…The necessary information and experimental data for all ground state isotopic combinations can be found in Ref. [15].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, achieving large Rabi frequencies, as required by our proposal, poses no problem for 171,173 Yb (ref. 42).…”
Section: Methodsmentioning
confidence: 99%